Review paper (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)

(untitled) - Rykała, Jan; Szychta, Paweł; Witmanowski, Henryk
The authors present physical properties of laser light, operating principles, kinds of lasers and also physical and biochemical bases of biological laser light action on human cells, tissues and living organisms. The authors discuss a broad range of biological mechanisms of laserotherapy, which were examined on different levels (cell, tissue, organ) and which let them explain the positive influence of laser light in different diseases. Currently known therapeutic effects of lasers may be in many cases beneficial, allowing for effective rehabilitation of the chronically ill, the possibility of replacing hospital-based surgery with outpatient conservative treatment (which is significantly shorter and the costs are reduced), as well as creating opportunities for the treatment of diseases as yet incurable.